Successive pretreatment and enzymatic saccharification of sugarcane bagasse in a packed bed flow-through column reactor aiming to support biorefineries - Terán-Hilares R. (2016)
The authors gratefully acknowledge the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCyTEC-Perú, process number 219-2014) and Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq-Brazil, process number 449609/2014-6) for financial support.